Photojournal: distant beats: tradition and change in senegal - Yacher, Leon (Focus on Geography, 2010)
Keywords: Senegal; cultural change; cultural geography; cultural influence; cultural landscape; cultural tradition; dept.egm; music

Geography in Peru - Yacher, Leon (The Professional Geographer, 1989)
Keywords: dept.egm

Marriage Migration and Racial Mixing in Colonial Tlazazalca, (michoacán, Mexico), 1750-1800 - Yacher, Leon I. (Discussion paper series (Syracuse University. Department of Geography) ; no. 32, 1977)
Keywords: Case studies; Case studies; Endogamy and exogamy; Marriage; Mexico; Tlazazalca (Michoacán); dept.egm; faculty_collection

Sabbatical leave report: sabbatical Spring 2010 - Yacher, Leon I. (2010)
The purpose of the project was to travel to Paraguay to explore the history of geography as a science in that country, including identifying the foremost geographers who helped introduce and establish geography as a science in that country. No such study on the history of geography in Paraguay had been previously undertaken anywhere. Further research will be needed, but the collected material is ample for at least two article-length publications.
Keywords: dept.egm; faculty_collection

The Role of Geographer and Natural Scientist Henri Francois Pittier (1857-1950) in the Evolution of Geography as a Science in Costa Rica - Yacher, Leon I. (Mellen studies in geography ; v. 12, 2004)
Keywords: Costa Rica; History; History; Geography; Influence; Geography; Latin America; Pittier, Henri, 1857-1950; award_winner; dept.egm

Henry's F. Pittier's Contributions to the Geography of Costa Rica and Venezuela. - Yacher, Leon I. (1995)
Keywords: dept.egm; faculty_collection; sabbatical_report

History of Geography as a Science in the Republic of Paraguay. - Yacher, Leon I. (2010)
Keywords: dept.egm; faculty_collection; sabbatical_report

Astana, Kazakhstan: Megadream, Megacity, Megadestiny? - Yacher, Leon (Engineering Earth: The Impacts of Megaengineering Projects, 2011)
Astana, Kazakhstan’s new capital city is being built to fit the future vision of the country’s leaders. Unique architectural styles, combined with creative morphological patterns give the city a distinctive look. It is being constructed to impress. It also represents a break from the past. As such, Astana embodies the meaning of a ‘Forward city.’ Forward cities are created for a variety of reasons; political, geopolitical, religious, economic or a combination of these. By relocating a capital city elsewhere, a country seeks to construct a fresh urban site that reflects a change from the traditional center of governmental activities to a new location that reveals a new direction for the country and its people. This chapter provides a brief background of the political context and conditions existing in the region, followed by an overview of the city’s geographic base, and scrutinize the unique methods of finance used to construct Astana. Also, the planning and design of the city will be examined, paying special attention to the ways in which architecture has been utilized to construct a futuristic vision of a public project for domestic and international consumption.
Keywords: Capital City; Kyrgyz Republic; Presidential Decree; Soviet Republic; Special Economic Zone; dept.egm

The Kyrgyz Republic's Liminal Media: assessing a journalistic rite of passage - Manzella, Joseph C; Yacher, Leon (Journalism Studies, 2005)
In the Western world, the Kyrgyz Republic has been depicted as a democratic success story. Indeed, unlike other Central Asia nation states, the Kyrgyz media appears on the surface relatively free. This paper examines the Kyrgyz press in the context of journalistic ideologies, and suggests that the republic's media is going through an important transitional phase, the central stage of a journalistic rite of passage. Part of that transitional process is an ongoing ideological tug-of-war that awaits resolution. It is suggested that such resolution may occur only when the press becomes economically self-sustaining. © 2005 Taylor & Francis Group, LLC.
Keywords: Journalistic Ideologies; Kyrgyz Media; Rite of Passage; dept.egm

New haven, connecticut, from the air - Richason, F Benjamin; Yacher, Leon (Journal of Geography, 1981)
Keywords: dept.egm

Two new Peruvian species of Jaltomata (Solanaceae, Solaneae) with red floral nectar - Mione, Thomas; González, Segundo Leiva; Yacher, Leon (Brittonia, 2014)
Two new Jaltomata species (Solanaceae) of Peru that produce red floral nectar are described. Jaltomata neei of Department Cajamarca has 1–4 flowers per inflorescence, the campanulate corolla is green and then changes to blue, corolla lobes (5) and lobules (5) are equally prominent, a corona is lacking, five radial staminal-corolla thickenings create nectar troughs between, and the stigma is capitate. Jaltomata quipuscoae of Department Arequipa has solitary flowers, a purple, broadly crateriform, 5-lobed corolla, a corona on which nectar pools, a punctiform stigma, lacks corolla thickenings, and the mature fruit is whitish. Photographs, illustrations and tables are included that allow comparison with closely related species. © 2014, The New York Botanical Garden.
Keywords: Arequipa; Cajamarca; Jaltomata neei; Jaltomata quipuscoae; Peru; corolla color change; corona; dept.egm; lomas; protogyny; red nectar

Five new species of jaltomata (solanaceae) from cajamarca, peru - Mione, Thomas; Leiva, G Segundo; Yacher, Leon (Novon, 2007)
Five new suffrutescent to shrubby Jaltomata Schlechtendal species (Solanaceae) of the department of Cajamarca, Peru, are described and illustrated, Jaltomata contumacensis S. Leiva & Mione has a light green, urceolate-tubular corolla and grows in the province of Contumazá between 2530 and 3000 m; J. lanata S. Leiva & Mione has a whitish purple to pale purple, short-tubular corolla and grows in the province of San Pablo between 1850 and 2400 m; J. leivae Mione has a red-violet, urceolate corolla containing red nectar and grows in the province of Contumazá between 2560 and 2650 m; J. oppositifolia S. Leiva & Mione bas a white, broadly infundibular to rotate corolla and grows in province Chota between 2250 and 3090 m; and J. yacheri Mione & S. Leiva has a blue-purple, urceolate corolla and grows in province Hualgayoc at 3460 m. The fruits of two of these species are eaten by people.
Keywords: Edible fruit; Jaltomata; Magnoliophyta; Red nectar; Solanaceae; dept.egm

Faculty Bibliography - Clarie, Thomas C.; Koch, Róbert; Yacher, Leon I.; Sandomirsky, LNatalie (Southern Connecticut State University, 1978)
Keywords: Bibliography; Faculty; Southern Connecticut State University; dept.art; dept.egm; dept.lib; faculty_collection